2020
DOI: 10.1055/a-1274-9146
|View full text |Cite
|
Sign up to set email alerts
|

Bestimmung von Sexualsteroiden in abgestoßener Haut der Gila-Krustenechse (Heloderma suspectum)

Abstract: Zusammenfassung Gegenstand und Ziel Die Messung in Hautanhangsgebilden wie Haaren oder Klauen bei Säugern oder in Federn bei Vögeln wird zur nicht invasiven Bestimmung von Steroidhormonen angewendet. Ziel dieser Arbeit war, in einer Pilotstudie an der Gila-Krustenechse zu testen, ob die Messung von Sexualsteroiden in abgeschilferter Haut bei Reptilien zur Erfassung der endokrinen Gonadenfunktion bzw. zur Geschlechtsbestimmung eingesetzt werden kann. Material und Methoden Für die U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…A pilot study evaluated the levels of sex steroids in shed skin of Gila monsters. Overall, the authors concluded this method was not a reliable test for sex determination (Schuler et al ., 2020). Gila monster sex chromosomes, chromosome number, and chromosome morphology have been described (Pokorná et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study evaluated the levels of sex steroids in shed skin of Gila monsters. Overall, the authors concluded this method was not a reliable test for sex determination (Schuler et al ., 2020). Gila monster sex chromosomes, chromosome number, and chromosome morphology have been described (Pokorná et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%